2017
DOI: 10.3389/fpls.2017.01281
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene Responses and Functions in Plants Challenged by Environmental Pressures Associated to Climate Change

Abstract: The functional reasons for isoprene emission are still a matter of hot debate. It was hypothesized that isoprene biosynthesis evolved as an ancestral mechanism in plants adapted to high water availability, to cope with transient and recurrent oxidative stresses during their water-to-land transition. There is a tight association between isoprene emission and species hygrophily, suggesting that isoprene emission may be a favorable trait to cope with occasional exposure to stresses in mesic environments. The suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 100 publications
0
38
0
2
Order By: Relevance
“…Across species, we also observed that HSP production and isoprene emissions during the heatwave were inversely related (Figure ). Our interpretation is that maintenance of lower T leaf and higher isoprene emissions during heatwave conditions results in less damage and stress, a reduced requirement for protection from HSPs, and weaker acclimation of T max (Fini et al, ; Siwko et al, ). Together, these data provide a integrative framework linking biochemical, physiological, and whole‐tree responses to species capacity to tolerate heatwave conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Across species, we also observed that HSP production and isoprene emissions during the heatwave were inversely related (Figure ). Our interpretation is that maintenance of lower T leaf and higher isoprene emissions during heatwave conditions results in less damage and stress, a reduced requirement for protection from HSPs, and weaker acclimation of T max (Fini et al, ; Siwko et al, ). Together, these data provide a integrative framework linking biochemical, physiological, and whole‐tree responses to species capacity to tolerate heatwave conditions.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the recent synthesis study by Fini et al. () found that some isoprene emitters do not respond to mild and moderate drought‐induced depressions of stomatal conductance, whole some decrease, and others increase, their emissions. There is a clear need for added research on VPD and drought impacts on VOC emissions with an emphasis on understanding the basic mechanisms that may explain such heterogeneity among species.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of water stress impacts have been conducted on different species, and the responses of isoprene emissions to such stress have not been consistent across studies, suggesting that the underlying mechanisms are not well understood. For example, the recent synthesis study by Fini et al (2017) found that some isoprene emitters do not respond to mild and moderate drought-induced depressions of stomatal conductance, whole some decrease, and others increase, their emissions. There is a clear need for added research on VPD and drought impacts on VOC emissions with an emphasis on understanding the basic mechanisms that may explain such heterogeneity among species.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…For instance, alien species of Hawaii emit more monoterpenes than native ones, and this has been suggested to be an indication of greater evolutionary success of alien species since monoterpene emission is associated with higher stress resistance [22]. More specifically, it was shown that isoprene biosynthesis evolved as an ancestral mechanism in plants to cope with transient oxidative stresses during their water-to-land transition [23]. Indeed, fast-growing hygrophilous Quercus species, such as most North American and some European oaks (e.g., Quercus robur), emit isoprene, whereas isoprene is replaced by monoterpenes in xeric oaks, such as Q. ilex [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, it was shown that isoprene biosynthesis evolved as an ancestral mechanism in plants to cope with transient oxidative stresses during their water-to-land transition [23]. Indeed, fast-growing hygrophilous Quercus species, such as most North American and some European oaks (e.g., Quercus robur), emit isoprene, whereas isoprene is replaced by monoterpenes in xeric oaks, such as Q. ilex [23,24]. In particular, it has been shown that ocimene is a commonly emitted monoterpene under stress conditions, in particular under heat stress [24].…”
Section: Introductionmentioning
confidence: 99%